Modification of wheat bran insoluble and soluble dietary fibers with snail enzyme - Xin Liu; Keke Suo; Pei Wang; Xue Li; Limin Hao; Jiaqing Zhu; Juanjuan Yi; Qiaozhen Kang; Jinyong Huang; Jike Lu (Food Science and Human Wellness)
Insoluble dietary fiber (IDF) and soluble dietary fiber (SDF) extracted from wheat bran were modified by snail enzyme and their physicochemical properties (water retention capacity and oil retention capacity), functional properties (cholesterol adsorption capacity, glucose adsorption capacity and antioxidant activity) and structural characterizations were evaluated. The results showed that snail enzyme modification led to the significant increase in oil retention capacity of IDF, glucose adsorption capacity and cholesterol adsorption capacity of IDF and SDF. Enzymatic modification also markedly improved the DPPH radical scavenging capacity and reducing power of IDF and SDF. Meanwhile, scanning electron microscopy (SEM) analysis indicated the microstructures of IDF and SDF powders were significantly changed. Fourier transfer-infrared spectrometry (FT-IR) showed that snail enzyme modification could degrade the part of cellulose and hemicellulose of IDF and SDF. All these improved physicochemical and functional properties of IDF and SDF might depend on their structural changes. It suggested that snail enzyme modification could effectively improve physicochemical and functional properties of IDF and SDF from wheat bran.